KARAKTERISTIK ANATOMI DAUN DARI SEPULUH SPESIES Hoya SUKULEN SERTA ANALISIS HUBUNGAN KEKERABATANNYA - Hafiz, Putra; Dorly, Dorly; Rahayu, Sri (Buletin Kebun Raya, 2013)
Hoya has two types of leaves, succulent and non succulent. Succulent plant adapted well in extreme conditions, especially during dry period. Anatomical characters can be used to identify, classify, and determine plant relationship. The aims of this research were to identify anatomical character of succulent Hoyaâs leaf and to determine their relationship. Ten examined species Hoya spp. (H. diversifolia, H. latifolia, H. dolichosparte, H. bilobata, H. lacunosa, H. verticillata, H. purpureofusca, H. kuhlii, H. oblanceolata, and H. micrantha) showed anatomical similarity in their epidermal layer, hipodermal, mesophyl, and the absence of sponge tissue at mesophyl. However, there are diversities among the species. Based on paradermal section of the leaf, Â two types of stomata were only found at the abaxial side, individual stomata and both individual and stomatal cluster. Hoya diversifolia has the smallest stomatal size, while Hoya latifolia has the biggest. Hoya lacunosa has the lowest stomatal density, while Hoya bilobata has the highest. Hoya diversifolia, Hoya lacunosa, and Hoya oblanceolata have the lowest stomatal index, while Hoya bilobata has the highest. Observation on transversal section showed that Hoya purpureofusca has the lowest leaf thickness, while Hoya kuhlii has the highest. The hierarchical cluster analysis based on anatomical leaf characters showed different patterns of relationship which diversed as three groups at relationship scale 15.